(untitled) (ALKIMIA : Jurnal Ilmu Kimia dan Terapan, 2024)
Rice-washing wastewater has the potential as a raw material for making bioethanol because it still contains carbohydrates. Adding NPK with the appropriate fermentation time can affect the levels of bioethanol produced. This study aims to determine the effect of the addition of NPK and fermentation time on the levels of bioethanol produced in the manufacture of bioethanol from rice-washing wastewater. Variations in the amount of NPK (5, 10, and 15 g) and variations in fermentation time (3, 5, and 7 days) are seen in their effect on the yield and characteristics of the bioethanol produced. The characteristics of bioethanol include content, specific gravity, API Gravity (American Petroleum Institute), calorific value, water content, density measurement with a densitometer instrument and qualitative analysis of bioethanol with a gas chromatography instrument. The highest bioethanol yield was 34% with the treatment of variations in adding 15 g of NPK and a fermentation time of 7 days. Based on the two-way ANOVA test results, the addition of NPK (5, 10, and 15 g) and the difference in fermentation time (3, 5, and 7 days) significantly affected the levels of bioethanol produced from rice-washing wastewater. The addition of 15 g of NPK and a fermentation time of 7 days provided the best bioethanol characteristics, with a bioethanol content of 20.84%. Using rice-washing wastewater with NPK and optimal fermentation time provides another alternative in developing bioethanol raw materials.